The Level of Social Responsibility among Najran University Students - Mohammed, Mahmoud Mustafa; Mohammed, Mohammed Maher (Migration Letters, 2024)
This research focuses on university students as important stakeholders in the higher education system. The main objective was to assess the level of social responsibility among students at Najran University and examine whether it varies based on variables such as gender, major, GPA, and academic level. The study utilized a descriptive methodology to achieve its goals, and fieldwork was conducted through an electronic survey distributed to a group of male and female students at Najran University. A total of 319 valid questionnaires were collected, and processed using SPSS software. The study found that the level of social responsibility was high. The dimension of self and ethical commitment towards society ranked highest with an average of (2.81) and a "large" degree. Following that, the dimension of concern for others with an average of (2.75) in the second position, also with a "large" degree. The dimension of community affiliation and its values and traditions ranked last with an average of (2.57) and a "large" degree. Additionally, the study revealed statistically significant differences at a significance level of (0.05) concerning the overall level of social responsibility among Najran University students based on variables such as gender, GPA, and academic level. However, no significant differences were found based on the major variable.